Central Banks Digital Currencies for Cross-Border Payments: Interoperability Models and Implementation Possibilities - D. A. Kochergin (Финансы: теория и практика)
The study is devoted to the use of central bank digital currencies in cross-border settlements. The purpose of the paper is to identify the capacity of cross-border settlements using multi-CBDC/mCBCD mechanisms based on different interoperability models. The study identified the main problems of modern cross-border settlements and the possible risks associated with the implementation of mCBDCs. The features of various models of interoperability in mCBDCs arrangements are revealed and prospects of their use are defined. It was concluded that the main problems of traditional cross-border settlements are legacy technology platforms, fragmented data presentation formats; complex processing of compliance checks; long transaction chains and etc. It was identified that the main risks associated with the implementation of mCBDCs are: “digital dollarization”, international “spillover effects” of economic and financial shocks, the use of digital currency for tax evasion and supervision of the domestic monetary system and financial market, etc. The obtained results allowed us to conclude that among the three main models of interoperability of mCBDCs, the single system model is the most prospect, since it allows to mitigate of cross-border and cross-currency risks, expand opportunities for infrastructure integration and technical compatibility, reduce the number of intermediaries and improves the security of settlements. In order to successfully implement mCBDC projects, in addition to the chosen operating model, a sufficiently high overall level of technological and infrastructural development of national CBDC systems, as well as economic and geopolitical interest in carrying out cross-border settlements between participating countries.